The Nuclear Pore Complex and mRNA Export in Cancer - Borden, Katherine L. B. (Cancers (Basel), 2020)
SIMPLE SUMMARY: There are multiple processes that can go awry to drive cancer. One of these arises from a dysregulation of trafficking of cellular materials between the two major compartments of the cell—the nucleus and the cytoplasm. These compartments are separated by a membrane or “wall”, but in this wall reside a series of tunnels, or pores, that permit specific materials to transit. One of these materials, known as RNA, carries the information from the nucleus to the cytoplasm to make proteins that can act in certain cellular processes such as growth or survival. If these RNAs transit between compartments inappropriately, they can cause dysregulation of a wide array of cellular processes, which in turn can contribute to cancer. This review describes the relevant pathways and presents strategies to target this process in cancer. ABSTRACT: Export of mRNAs from the nucleus to the cytoplasm is a key regulatory step in the expression of proteins. mRNAs are transported through the nuclear pore complex (NPC). Export of mRNAs responds to a variety of cellular stimuli and stresses. Revelations of the specific effects elicited by NPC components and associated co-factors provides a molecular basis for the export of selected RNAs, independent of bulk mRNA export. Aberrant RNA export has been observed in primary human cancer specimens. These cargo RNAs encode factors involved in nearly all facets of malignancy. Indeed, the NPC components involved in RNA export as well as the RNA export machinery can be found to be dysregulated, mutated, or impacted by chromosomal translocations in cancer. The basic mechanisms associated with RNA export with relation to export machinery and relevant NPC components are described. Therapeutic strategies targeting this machinery in clinical trials is also discussed. These findings firmly position RNA export as a targetable feature of cancer along with transcription and translation.